CURRENT STATUS OF RAINFED GRAY SOIL AND WAYS OF USING THEM - Akramovna, Gafurova Lazizakhon; Muratkasimov, Alisher Sattarovich; Yusupovich, Yusupov Hasan; Yuldashevna, Mahkamova Dilafruz; Khaliqjanovna, Ergasheva Olimakhon; Xalilovna, Hakimova Muabara (International Journal of Psychosocial Rehabilitation, 2020)
The results of the study on the efficiency of organic and mineral fertilizers, absorbents, and biologically active substances in the conservation of soil fertility in dehydrated rain-fed areas of our Republic after 2nd year of dew, nutritional management of soil moisture.